ANALISIS PROFIL WISATAWAN OBJEK WISATA GAZEBO DI DESA WISATA KEMETUL KABUPATEN SEMARANG - Latifah, Adina Septiani; Hudiono, Rini Kartika (Universitas Kristen Satya Wacana, 2020)
This research determines tourist profile in tourist attraction of Gazebo in the Kemetul village tourism in Semarang. This research discusses socio-demographics condition, psyco-graphics condition, tourist expectation, and geography in Kemetul Village. This research conducted with the quantitative descriptive method using a survey. The survey conducted to 126 tourists as the existing market. The survey result shows that most of the visitors of Gazebo Kemetul Village are students with age between 15-25 years old, and dominated with visitors who came from Semarang City. The result shows that 40% of visitors like artificial tourist attraction, 58% tourist like solo travelling. Research also found that most of the visitors are hoping the regional government or the manager of the Kemetul village will able to add a playground and local culinary corner at Gazebo Kemetul Village.